1977
DOI: 10.1128/iai.16.1.174-180.1977
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Responsiveness to Escherichia coli During Pregnancy

Abstract: To determine whether immunological responsiveness to a bacterial antigen is altered during pregnancy and lactation, Swiss mice (gestation, 19 to 21 days) were studied during early, middle, and late pregnancy and in the early postpartum period. Pregnant and nursing mice, each along with a virgin female littermate control, were injected with 2 x 106 heat-killed Escherichia coli and sacrificed 4 days later for the enumeration of splenic anti-E. coli plaque-forming cells (PFC). For 72 4to 10-day pregnant and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Administration of a larger bacterial inoculum or another schedule and route of immunization may have improved the antibody response in these adult rats. It is unlikely that pregnancy altered this immune response, since Kenny and Diamond have shown that pregnant rats have enhanced antibody production after immunization with various bacterial antigens when compared with nonpregnant control animals (14).…”
Section: Resultsmentioning
confidence: 99%
“…Administration of a larger bacterial inoculum or another schedule and route of immunization may have improved the antibody response in these adult rats. It is unlikely that pregnancy altered this immune response, since Kenny and Diamond have shown that pregnant rats have enhanced antibody production after immunization with various bacterial antigens when compared with nonpregnant control animals (14).…”
Section: Resultsmentioning
confidence: 99%
“…A decreased maternal immunoreactivity during pregnancy, contributing to tolerance of the fetal allograft, has been suggested frequently (6). Humoral immunity is either not affected or even slightly stimulated during pregnancy (12,22,32). The decreased mixed-lymphocyte reaction, phytohemagglutinin stimulation, and lymphocyte cytotoxicity, as well as delayed rejection of cardiac allografts, during pregnancy reflect impairment of T-cell function in vitro and in vivo (3,8,15,16,28,42).…”
mentioning
confidence: 99%
“…While neutralizing antibodies have been reported in the sera of pregnant women following therapeutic vaccinationl'<'" and natural infection,22-24 animal experiments monitoring specific antibody-producing cell and immunoglobulin levels following immunization provide contrasting information, depending largely on the T-dependence or otherwise of the antigen involved and the route of inoculation. [25][26][27][28][29] The most convincing evidence for B-cell activity during human pregnancy comes from observations of maternal anti-paternal antibodiesv? and maternal anti-idiotype antibodies!"…”
Section: Discussionmentioning
confidence: 99%